The genetics of pediatric brain tumors - Dubuc, Adrian M.; Northcott, Paul A.; Mack, Stephen; Witt, Hendrik; Pfister, Stefan; Taylor, Michael D. (Current neurology and neuroscience reports, 2010)
Brain tumors are the most common childhood solid malignancy and the leading cause of cancer-related death in children. Medulloblastoma, ependymoma, supratentorial primitive neuroectodermal tumors, and pilocytic astrocytoma are the most prevalent types, all of which are clinically, histologically, and genetically heterogeneous. Despite an incomplete molecular understanding of these tumors, we have made significant headway in the past 5 years in identifying and classifying important genetic alterations and pathways central to the disease process. This review summarizes our current state of knowledge, emphasizes recent seminal findings in the field, and proposes future research efforts needed to further characterize the genetic basis of pediatric brain tumors.
Gesehen am 20.02.2023